Implementasi Pencatatan Persediaan Barang Dagang Berdasarkan SAK pada Bisnis Minimarket di Kota Batam - Puspita Rama Nopiana; Dede Kritian Putra Halawa; Yetina Halawa; Ernita Zega (Universitas 45 Surabaya, 2025)
Starting from the problem of MSMEs, especially the minimarket business, Mrs. Helty explained that she did not know about information on incoming and outgoing goods, did not have employee knowledge, could not determine sales turnover targets and could not control expired goods. So the purpose of this PKM is to petrify businesses so that the problems faced can be solved. The method of implementing this activity is lectures, exercises and discussions as well as guidance to employees specifically in calculating the cost of goods sold. The results of PKM conducted tutoring on inventory recording with periodic methods in the assessment of FIFO (First In First Out) and LIFO (Last In First Out) inventory with certain coding. This PKM can also assist owners in managing their business starting from planning, organizing, controlling and evaluating businesses to be better in the future. It is recommended to owners to be able to implement the results of the training so that business goals are achieved. Furthermore, it can also develop and control businesses with computerized systems, especially for the merchandise inventory system.